2017
DOI: 10.3389/fmicb.2017.01371
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Microbial Community Dynamics in Microbial Electrolysis Cells – Influence of Acetate and Propionate Concentration

Abstract: Microbial electrolysis cells (MECs) are widely considered as a next generation wastewater treatment system. However, fundamental insight on the temporal dynamics of microbial communities associated with MEC performance under different organic types with varied loading concentrations is still unknown, nevertheless this knowledge is essential for optimizing this technology for real-scale applications. Here, the temporal dynamics of anodic microbial communities associated with MEC performance was examined at low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…This result was in agreement with another study [33], where Desulfovibrio was present in a high relative abundance as a planktonic member, although the same authors also identified this genus on their enriched electrodes in previous work [34]. Desulfovibrio has been mainly described as a biological hydrogen producer [32], and its presence along with Pseudomonas, both belonging to the Proteobacteria phylum, has been described in other MES systems [35]. Regarding Pseudomonas, there is physiological evidence that it can develop hydrogenase activity [36] and produce shuttles in BES, thus potentially playing an important role in the extracellular electron transfer [23,37].…”
Section: Discussionsupporting
confidence: 91%
“…This result was in agreement with another study [33], where Desulfovibrio was present in a high relative abundance as a planktonic member, although the same authors also identified this genus on their enriched electrodes in previous work [34]. Desulfovibrio has been mainly described as a biological hydrogen producer [32], and its presence along with Pseudomonas, both belonging to the Proteobacteria phylum, has been described in other MES systems [35]. Regarding Pseudomonas, there is physiological evidence that it can develop hydrogenase activity [36] and produce shuttles in BES, thus potentially playing an important role in the extracellular electron transfer [23,37].…”
Section: Discussionsupporting
confidence: 91%
“…From the perspective of wastewater treatment with resource recovery, EAB that are highly specialized seem to be more efficient in terms of CE and current density. For instance, Geobacter sulfurreducens , a model EAB, is highly specialized and is currently considered the most important current-producing bacterium, and it is the most commonly identified anodic EAB derived from municipal wastewater in microbial fuels cells (MFCs) or microbial electrolysis cells (MECs), using acetate containing growth medium 6 , 7 , 15 , 16 . G. sulfurreducens interact with the anode by direct electron transfer using outer membrane cytochromes 17 and nanowires 18 to externalize the electrons from cell to the anode.…”
Section: Introductionmentioning
confidence: 99%
“…The anode biofilm is a complex aggregation of microbial communities and substances developed from planktonic microorganisms attached to the anode surface. It has been found that several factors can affect the formation, structure, and performance of anode biofilms, including the substrate concentration ( Hari et al, 2017 ), electron acceptor ( Ucar et al, 2017 ), anode solution ( Liu et al, 2017 ), electrode potential ( Bosire and Rosenbaum, 2017 ), and electric field intensity ( Du et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%